Ijtihad Kontemporer: Telaah Kritis atas Relasi Teks dan Realitas - Muhamad Saefullah (Syariah: Journal of Fiqh Studies, 2026)
The advancement of age, marked by significant transformations in social structures, cultural patterns, and modes of life, has generated new challenges for Islamic law, particularly in addressing contemporary issues that are not explicitly accommodated within the corpus of classical fiqh. This article aims to analyze the urgency of contemporary ijtihād as a methodological instrument for formulating Islamic legal responses that are comprehensive, contextual, and responsive to the dynamics of the age. Employing a normative-critical library research approach, the study argues that ijtihād cannot be undertaken in a partial or fragmented manner; rather, it must be integrative, grounded in a constructive synergy between the classical principles of uṣūl al-fiqh and contemporary scientific approaches, including the model of istiṣlāḥ. Interdisciplinary collaboration and the active engagement of scholars from diverse fields of expertise are essential prerequisites for producing legal formulations that are not only textually valid but also socially responsive. The findings suggest that an integrative model of contemporary ijtihād holds significant potential to generate an applicable and solution-oriented fiqh while simultaneously advancing public welfare in harmony with the objectives of the sharīʿah. Accordingly, methodological renewal in ijtihād constitutes a strategic step toward actualizing Islamic normative ideals within the context of contemporary society.